Melting and solidification of lead nanoparticles embedded in Aluminium-Gallium matrices. (15th April 2017) - Peterlechner, M.; Moros, A.; Rösner, H.; Lazar, S.; Ericus, P.; Wilde, G.
Abstract: Analyzing the impact of the host matrix on the melting/solidification of embedded Pb nanoparticles, various Ga concentrations (0, 1, 3 and 6 at.%) were added to the Al matrix within the solid solution regime to modify the mismatch between matrix and nanoparticles by expanding the host lattice. Using transmission electron microscopy and differential scanning calorimetry, a strong impact of an atomically flat Ga-enriched wetting layer around the Pb nanoparticles on the melting/solidification was observed. The Ga-enrichment was found to be about ∼3% above the matrix level, independent of the Ga concentration in the matrix. It is concluded that upon solidification vacancies arising from the 3.3% volume shrinkage of liquid Pb are filled by the fast diffusing Ga. The Ga-enriched layer chemically and mechanically decouples the matrix from the nanoparticles leading to a more freestanding particle behavior showing strong undercooling upon solidification and reduced or no superheating upon melting.